Learning Evaluation in Islamic Religious Education Subjects to Measure the Effectiveness of Elementary School Teachers’ Teaching Strategies - Bandono, Adi; Gunawan, Wawan; Sitompul, Nurmida Chaterine; Zubir, Nor Maizatul Akmal Binti Mohd; Listyowati, Iswahyuni (Al Irsyad: Jurnal Studi Islam, 2026)
The research problem shows that the evaluation of Islamic Religious Education learning is still dominated by the cognitive aspect, which limits its ability to measure affective and psychomotor aspects, and has not been optimal in improving the overall quality of teachers’ instruction. This study aims to determine the influence of formative and summative evaluation, as well as learning motivation, on the effectiveness of Islamic Religious Education teachers’ teaching methods in the overall learning process. The method used is quantitative research with an experimental approach through questionnaires distributed to 80 Islamic Religious Education teachers. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 27, with a two-way analysis of variance to examine the influence of evaluation and learning motivation. The results show that evaluation methods and learning motivation have a significant influence on the effectiveness of Islamic Religious Education teachers’ instruction, with a significance value of 0.000, an evaluation value of 128.808, and a motivation value of 39.366. In addition, there is a significant interaction effect (41.473), indicating that the effect of evaluation depends on the level of motivation. Summative evaluation is generally more effective at measuring learning outcomes than formative evaluation, whereas formative evaluation is more effective for teachers with high motivation. In conclusion, adjusting formative and summative evaluation based on learning motivation improves the effectiveness of Islamic Religious Education learning and optimally and measurably enhances the quality of teachers’ instruction. The significance of this study lies in its theoretical and practical contributions to the development of more holistic Islamic Religious Education evaluation and to the continuous improvement of teacher competence through professional development.